Consolidated extension projects, the documentary heritage of the city of Mar del Plata (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
The present work is part of a series of consolidated extension projects that allowed the creation and establishment of new links between the Faculty of Humanities of the National University of Mar del Plata, the Municipality of the General Pueyrredón Party and the Province of Buenos Aires, in the field of management of institutions such as theater and museums. In particular, these projects have focused on the systemic approach to their documentary heritage, which is difficult access by the community, associated with the activities and the institutional and cultural life of each one of them. The theoretical analysis from the informative-documentary perspective, its diagnosis, and the practical approach of the special collections that constitute the heritage of museums and arts centers make it possible to achieve of differentiated documentary management systems in accordance with each institution and at the same time generate protocols of work applicable and replicable partially or totally in other similar organizations.
Keywords: Documentary Heritage; University Extension; Cultural Management